Performance Audit of District Hospitals in Arunachal Pradesh - CAG of India (CAG of India, 2020)
This stand alone report of the CAG of India contains results of Performance Audit of District Hospitals in Arunachal Pradesh covering the period 2014-15 to 1018-19. In this Performance Audit we have focused on the patient care given by the primary and secondary care levels in the State. We assessed the availability of basic infrastructure facilities in the State, adequacy of manpower in the selected District Hospitals and various services provided therein like Out Patient and In-Patient Services, Maternity Services, Emergency Services, Drug Management, Infection Control, Bio-medical Waste Management, Diagnostic Services, Fire Control measures etc, based on pre-determined performance indicators/ criteria in the sampled district level and block level hospitals (CHC & PHC). We have adopted Indian Public Health Standard (IPHS) prescribed by the Government of India and adopted by the Government of Arunachal Pradesh which are a set of uniform standards envisaged to improve the quality of health care delivery in the country as well as State norms as applicable for benchmarking various audit findings.
For the Period 2014-15 to 2018-19